2015
DOI: 10.1093/aje/kwu321
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Level and Longitudinal Study of Adolescent Mothers and Intergenerational Maltreatment

Abstract: For teenage mothers in California, we generated population-level estimates of the relationship between maternal history of maltreatment and next-generation abuse and neglect. California birth records for all infants born to primiparous teen mothers in 2006 or 2007 were linked to statewide child protective services (CPS) records. For each birth, we used CPS records to document 1) whether the teen mother had a history of reported or substantiated maternal maltreatment at or after age 10 years and before the esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 36 publications
3
44
1
2
Order By: Relevance
“…Maltreatment was substantiated in only 18% of CPS investigations . A growing body of research, however, indicates the fallibility of substantiation decisions and points to heightened rates of various adversities in the broader population of children reported to CPS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maltreatment was substantiated in only 18% of CPS investigations . A growing body of research, however, indicates the fallibility of substantiation decisions and points to heightened rates of various adversities in the broader population of children reported to CPS …”
Section: Introductionmentioning
confidence: 99%
“…Early sexual debut, multiple partners and unprotected sexual activity place adolescents at risk of adverse outcomes, including heightened rates of pregnancy and increased rates of STDs . Although the birthrate among adolescents in the United States is at an all‐time low (a finding observed across age and racial and ethnic groups), adolescent pregnancy continues to be a significant public health concern because of its association with poor outcomes for both mothers and children …”
mentioning
confidence: 99%
“…Yet, there is a growing body of research linking the experience of child maltreatment (as indicated by CPS involvement) in later childhood or adolescence to the increased likelihood of involvement as a parent in CPS (Thornberry & Henry, 2013). Most recent data from California indicates at least a 44% increased likelihood that a mother who conceives between the ages of 15-19 will be reported for child maltreatment before her child reaches five years of age (Putnam-Hornstein, Cederbaum, King, Eastman, & Trickett, 2015).…”
Section: Caregiver Traumatic Stressmentioning
confidence: 99%
“…The prevalence of this cycle of risk was demonstrated in a recent population-level, longitudinal study of the relationship between adolescent pregnancy, maternal history of maltreatment, and intergenerational abuse and neglect (Putnam-Hornstein, Cederbaum, King, Eastman, & Trickett, 2015). Among 85,084 births to adolescents (aged 15–19) in California during 2006 and 2007, 28% were to a mother who had been maltreated between 10 years of age and her conception date (this figure included both unsubstantiated and substantiated reports).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of abuse and neglect for children of mothers who had previously been maltreated was significantly higher than the rate of abuse and neglect for children of mothers who had not been previously mal-treated. Thus, the mother’s experience of maltreatment was a strong predictor of maltreatment within the next generation (Putnam-Hornstein et al, 2015). To decrease the likelihood of intergenerational cycles of child abuse and neglect and associated risk factors, it is critical for child welfare services to address the needs of adolescent parents in order to prevent recidivism and improve parenting skills among referred adolescent-led families.…”
Section: Introductionmentioning
confidence: 99%